To simplify the expression \(-3.6 \div (-60)\), we start by performing the division.
\[ -3.6 \div (-60) = \frac{-3.6}{-60} \]
When dividing two negative numbers, the result is positive:
\[ \frac{-3.6}{-60} = \frac{3.6}{60} \]
Now, we can simplify \(\frac{3.6}{60}\).
First, convert \(3.6\) to a fraction:
\[ 3.6 = \frac{36}{10} \]
Thus,
\[ \frac{3.6}{60} = \frac{36/10}{60} = \frac{36}{10 \times 60} = \frac{36}{600} \]
To simplify \(\frac{36}{600}\), we can divide both the numerator and the denominator by 12:
\[ \frac{36 \div 12}{600 \div 12} = \frac{3}{50} \]
Calculating \(\frac{3}{50}\) gives:
\[ 3 \div 50 = 0.06 \]
Therefore, the simplification of \(-3.6 \div (-60)\) results in:
\[ 0.06 \]
Thus, the answer is:
\(\boxed{0.06}\)